SELF-DEFENSE WITH THE TEACHING METHODS OF PERFORMANCE - Mališa Radović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
Self-defense skills are old as humankind. From time immemorial and even today in civilized world, people have been trying to find and develop the skills to protect themselves from the attacker. Self-defense is a sort of fight, whose cause is to disable an armed, unarmed, one or more opponents with the use of gained knowledge, habits or skills. During the training process, i.e. exercise process, it is necessary to train well every single move before practical use of a skill. Self-defense demand persistent and longtime exercises, fast, precise and timely performance of the appropriate techniques. Otherwise, the performance of even the best technique will not be successful. A person who practices self-defense techniques should establish ethics in fight, so that the opponent, except if unavoidable, is never being hurt.